Joint formation in ultrasonic spot welding of aluminum to copper and the effect of particle interlayer. (February 2020) - Ni, Z.L.; Yang, J.J.; Gao, Z.T.; Hao, Y.X.; Chen, L.F.; Ye, F.X.
Abstract: Ultrasonic spot welded Al/Cu joints with and without Al2219 particle interlayer are successfully achieved. For the Al/Cu joints, as the welding energy increases, the T-peel failure load increases up to the maximum value at the welding energy of 1500 J, and then decreases; the hardness at the center of the cross-section is lower than that of the base metal; micro-joints expand until a strong interface bonding is established, excessive welding energy promotes the formation of sonotrode tip sticking. Under the action of Al2219 particle interlayer, significant mechanical interlocking and swirl-like flow are generated at the weld interface. The maximum T-peel failure load (336.8 N) of Al/Al2219/Cu joint is 32.3 % higher than that (254.6 N) of Al/Cu joint.